Agrometeorological advisory services for improved climate resilience in Africa - Lobote, Lys; Asnake, Asaye; Lemma, Esayas; Ceccarelli, Tomaso (Technical Centre for Agricultural and Rural Cooperation, 2019)
Agriculture is the backbone of Ethiopia and Mali and provides a living for most people in both countries. But climate change is already having an impact on food security as a result of increased extreme events and unpredictable weather patterns. Agrometeorological advisory services are helping some farmers to increase production despite the challenges.